Investigation of Efficient Mixing Enhancement in a Droplet Micromixer with Short Mixing Length at Low Reynolds Number - Yuanfang Qiu; Xueze Zhang; Mengzhen Hao; Xu Yin; Mengling Zhou; Shichao Ma; Yuanting Zhang; Naiqian Jiang; Li Xie; Xichen Yuan; Honglong Chang (Micromachines)
Rapid mixing is widely prevalent in the field of microfluidics, encompassing applications such as biomedical diagnostics, drug delivery, chemical synthesis, and enzyme reactions. Mixing efficiency profoundly impacts the overall performance of these devices. However, at the micro-scale, the flow typically presents as laminar flow due to low Reynolds numbers, rendering rapid mixing challenging. Leveraging the vortices within a droplet of the Taylor flow and inducing chaotic convection within the droplet through serpentine channels can significantly enhance mixing efficiency. Based on this premise, we have developed a droplet micromixer that integrates the T-shaped channels required for generating Taylor flow and the serpentine channels required for inducing chaotic convection within the droplet. We determined the range of inlet liquid flow rate and gas pressure required to generate Taylor flow and conducted experimental investigations to examine the influence of the inlet conditions on droplet length, total flow rate, and mixing efficiency. Under conditions where channel dimensions and liquid flow rates are identical, Taylor flow achieves a nine-fold improvement in mixing efficiency compared to single-phase flow. At low Reynolds number (0.57 ≤ Re ≤ 1.05), the chip can achieve a 95% mixing efficiency within a 2 cm distance in just 0.5–0.8 s. The mixer proposed in this study offers the advantages of simplicity in manufacturing and ease of integration. It can be readily integrated into Lab-on-a-Chip devices to perform critical functions, including microfluidic switches, formation of nanocomposites, synthesis of oxides and adducts, velocity measurement, and supercritical fluid fractionation.